Controlled Growth of the Noncentrosymmetric Zn(3-Ptz) 2 and Zn(Oh)(3-Ptz) Metal-Organic Frameworks - Herrera-Urbina, F; Singh, D; Enríquez-Montenegro, J; Manquián-Villalobos, C; Chi-Duran, I (American Chemical Society, 2019)
Noncentrosymmetric single-crystal metal-organic frameworks (MOFs) are promising candidates for phase-matched nonlinear optical communication. However, the typical hydrothermal synthesis conditions produce small crystals with relatively low transmittance and poor phase matching. In the search for optimal crystal morphology, we study the effect of the metal-to-ligand molar ratio and reaction pH on the hydrothermal synthesis of the noncentrosymmetric Zn(3-ptz) 2 and Zn(OH)(3-ptz) MOFs with in situ ligand formation. In acidic environments, we find that decreasing the amount of ligand below the stoichiometric molar ratio 1:2 also produces highly transparent single-crystal octahedrons of Zn(3-ptz) 2 . In alkaline environments, we obtain long rodlike Zn(OH)(3-ptz) crystals whose length exceeds previous reports by up to 4 orders of magnitude. All reaction products are characterized by using powder X-ray diffraction, Fourier transform infrared spectroscopy, optical and scanning electron microscopy, and solid-state UV-visible spectroscopy. Additionally, we find an alternative synthesis route for the recently reported high-energy MOF Zn(3-ptz)N 3 . Potential applications of these results in the development of MOF-based nonlinear optical devices are discussed. © 2019 American Chemical Society.